Dose Timing of an Angiotensin II Receptor Blocker/Calcium Channel Blocker Combination in Hypertensive Patients With Paroxysmal Atrial Fibrillation. Issue 10 (16th March 2016) - Kario, Kazuomi; Hoshide, Satoshi; Uchiyama, Kazuaki; Yoshida, Tetsuro; Okazaki, Osamu; Noshiro, Takao; Aoki, Hirotaka; Mizuno, Hiroyuki; Matsumoto, Yuri
Abstract : It has long been thought that there is a close association between hypertension and atrial fibrillation (AF). However, the efficacy of an angiotensin II receptor blocker for the prevention of organ damage in hypertensive individuals with AF is still controversial. The present study was a multicentered, prospective, randomized, open‐label clinical trial investigating the differences in the effect of treatment with telmisartan/amlodipine combination tablets on blood pressure (BP) levels and BP variability between morning and bedtime administration in hypertensive patients with paroxysmal AF, using ambulatory BP monitoring (ABPM) and home BP. With this treatment, the patients' 24‐hour BP, nighttime BP, preawake BP, and morning BP shown by ABPM were significantly reduced, and the antihypertensive effects were similar regardless of the timing of the drug administration. The standard deviation of day‐by‐day home systolic BP and the maximum home systolic BP were also significantly reduced, and these effects were similar regardless of the treatment timing. The N‐terminal pro‐brain natriuretic peptide level was significantly decreased only in the bedtime administration group. A larger study will demonstrate whether the bedtime administration of telmisartan/amlodipine combination tablets maximizes the risk‐lowering effect against AF recurrence in paroxysmal AF hypertensive patients.